Do enhanced efficiency potassium sources increase maize yield in soil with high potassium content? - Ribeiro, Bruno Neves [UNESP]; Roms, Rafael Zoccolaro [UNESP]; Coelho, Anderson Prates [UNESP]; Batista-Silva, Willian; Souza, Juscelio Ramos de; Gissi, Luciano De; Lemos, Leandro Borges [UNESP] (São Paulo - Escola Superior de Agricultura Luiz de Queiroz, 2022)
Enhanced efficiency potassium fertilizers can be a management tool that is crucial to crop sustainability in maize (Zea mays L.). However, there is a need for studies aimed at validating the use of these fertilizers in different production environments. This study aimed to evaluate the performance of maize under sources and rates of K through conventional and enhanced efficiency fertilizers in soil with high available K content. The experiment was carried out for two years in an Oxisol (605 g kg–1 of clay) with high K content (6.7 mmolc dm–3). Three sources were used, one conventional (KCl), one obtained by additives sprayed on the fertilizer surface (KCl-C), and one obtained by compacting KCl powder and adding additives (KCl-CC), associated with three K2O rates as top-dressing (50, 100, 150 kg ha–1) and a control without K2O. In all treatments, 48 kg ha–1 of K2O was applied in the sowing furrow. In the first year, maize yield increased linearly for both the KCl and KCl-C sources. The maximum yield (7,967 kg ha–1) for the KCl-CC was obtained at 88 kg ha–1. In the second year, the maximum yields for the KCl (7,553 kg ha–1) and KCl-C (8,166 kg ha–1) were obtained with 20 and 67 kg ha–1 K2O, respectively, while for the KCl-CC maize yield did not change. Enhanced efficiency K sources promote increases in maize yield ranging from 4.3 % to 7.1 %. Top-dressing K fertilization in high-fertility soils is a viable alternative for producers focused on increasing maize yield, mainly when enhanced efficiency sources are used.
Keywords: Zea mays L; potassium chloride; compacted source; slow release; grain yield